FAKTOR – FAKTOR YANG MEMPENGARUHI INITIAL RETURN (Studi Empiris Pada Perusahaan yang IPO di BEI Periode 2011-2020) - Kurnia, Anita; Widaryanti, Widaryanti; Latifah, Nurul (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
This study aims to analyze the effect of ROA, DER, EPS, company size and company age on initial return. The independent variables used in this study are the factors that affect the initial return. The dependent variable in this study is initial return. This study uses secondary data derived from annual financial statements. The population in this study are all IPO companies listed on the Indonesia Stock Exchange for the period 2011-2020. The sampling technique used is purposive sampling and the number of samples is 286 data. Data analysis method using multiple linear regression. The results of this study indicate that ROA, DER, and EPS have no significant effect on Initial Return. Firm Size and Company Age have a negative and significant effect on Initial Return.Keywords: ROA, DER, EPS, Company Size, Company Age and Initial Return